2020
DOI: 10.1038/s41598-020-76661-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of vascular complications in people with impaired fasting glucose: a national cohort study in Korea

Abstract: This study aimed to evaluate the risk of vascular complications of impaired fasting glucose (IFG). This population-based study included 425,608 participants from the National Health Screening Cohort in Korea in 2003 and 2004 who were followed-up until 2015. The participants were classified into normal, IFG, and diabetes groups based on fasting plasma glucose levels. Incidence rate (per 1000 person-year) was evaluated for the following vascular complications: cardiovascular (ischemic heart disease, cerebrovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Prevention of CKD and diabetes can only be done by managing the disease at impaired fasting glucose (IFG) and prediabetes levels. Impaired fasting blood sugar (IFG) is a pre-diabetic condition linked to a relatively elevated probability of developing diabetes2 (Yu et al, 2020). Early identification of prediabetes and individualised therapy are required to effectively manage this steadily increasing diabetic population.…”
Section: Prevention At the Level Of Impaired Fasting Glucose And Pred...mentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of CKD and diabetes can only be done by managing the disease at impaired fasting glucose (IFG) and prediabetes levels. Impaired fasting blood sugar (IFG) is a pre-diabetic condition linked to a relatively elevated probability of developing diabetes2 (Yu et al, 2020). Early identification of prediabetes and individualised therapy are required to effectively manage this steadily increasing diabetic population.…”
Section: Prevention At the Level Of Impaired Fasting Glucose And Pred...mentioning
confidence: 99%
“…Early identification of prediabetes and individualised therapy are required to effectively manage this steadily increasing diabetic population. IFG is a significant indicator of diabetes and its comorbidities (Yu et al, 2020). Consistently high blood sugar levels can cause heart problems, diabetic nephropathy, retinopathy, neuropathy, and increased https://journals.e-palli.com/home/index.php/ajcp Am.…”
Section: Prevention At the Level Of Impaired Fasting Glucose And Pred...mentioning
confidence: 99%
“…Nevertheless, the results of prospective studies can serve as indirect evidence in favor of the adverse effect of prediabetes on the state of both the arterial wall as a whole and the severity of atherosclerotic changes in it [ 31 , 32 , 33 ]. So, in a recent national cohort study in Korea, with a 12-year prospective observation, it was shown that the DM group showed the highest incidence and risk of vascular complications (cardiovascular, renal; and retinal), followed by the IFG group and the lowest risk was in group of normoglycemia [ 32 ]. It is clear that partly the intermediate risk of vascular complications in the prediabetes group could be associated with subsequent development of diabetes.…”
Section: Discussionmentioning
confidence: 99%